Analisis vegetasi tumbuhan angiospermae di desa ranga-ranga kecamatan masama kabupaten banggai - Nurlia Nurlia; Wahyudin Abd. Karim (Program Studi Pendidikan Biologi, Fakultas Pendidikan Ilmu Eksakta dan Keolahragaan, IKIP Budi Utomo Malang, 2020)
The structure and composition of vegetation are influenced by different types of plants, so vegetation constituent data is needed to determine the diversity of plant species. The purpose of this study was to determine the structure and composition of Angiosperms plant vegetation constituents in Ranga-ranga Village. The research method used was experimental with a type of exploratory descriptive research using a plot line method of 20 plots. The research instrument was an observation sheet. Research data namely the type and number of plants. Quantitative descriptive data analysis techniques to obtain the value of relative frequency, relative density, relative dominance, and index of important values. The results showed that the highest relative frequency of A. occidentale (FR = 31.03%), the lowest was R. communis, M. sago, A. carambola, T. cacao, M. indica, A. heterophyllus, S. lineatum, C. pulcherrima, and M. calabura (FR = 1.29%). The highest relative density of C. rotundus (KR = 31.39%), the lowest C. pulcherima and C. Arabica (KR = 0.89%). The highest relative dominance of T. grandis (DR = 16.15%), the lowest M. indica (DR = 4.67%). The highest importance index is A. occidentale (INP = 59.85%), the lowest is R. communis, A. carambola, M. indica, A. heterophyllus, C. pulcherrima, and M. calabura (INP = 2.33%). The conclusion of the research is the structure and composition of vegetation of Angiosperms plants in Ranga-ranga Village, varying at the level of trees, poles, saplings, and seedlings.